The Potential Effect of Nav1.8 in Autism Spectrum Disorder: Evidence From a Congenital Case With Compound Heterozygous SCN10A Mutations - Heinrichs, Björn; Liu, Baowen; Zhang, Jin; Meents, Jannis E.; Le, Kim; Erickson, Andelain; Hautvast, Petra; Zhu, Xiwen; Li, Ningbo; Liu, Yi; Spehr, Marc; Habel, Ute; et al. (Frontiers in Molecular Neuroscience, 2021)
Apart from the most prominent symptoms in Autism spectrum disorder (ASD), namely deficits in social interaction, communication and repetitive behavior, patients often show abnormal sensory reactivity to environmental stimuli. Especially potentially painful stimuli are reported to be experienced in a different way compared to healthy persons. In our present study, we identified an ASD patient carrying compound heterozygous mutations in the voltage-gated sodium channel (VGSC) Nav1.8, which is preferentially expressed in sensory neurons. We expressed both mutations, p.I1511M and p.R512*, in a heterologous expression system and investigated their biophysical properties using patch-clamp recordings. The results of these experiments reveal that the p.R512* mutation renders the channel non-functional, while the p.I1511M mutation showed only minor effects on the channel’s function. Behavioral experiments in a Nav1.8 loss-of-function mouse model additionally revealed that Nav1.8 may play a role in autism-like symptomatology. Our results present Nav1.8 as a protein potentially involved in ASD pathophysiology and may therefore offer new insights into the genetic basis of this disease.